Analysis learning evaluation in indonesian language subjects: An islamic educational perspective at grade v of sdn 16 bengkulu city - Ocei Fitri Pirmadi; Afifah Fadhila; Masrifa Hidayani; Intan Utami; Dalima Septiria (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Learning evaluation is an essential component of the educational process, including within the framework of Islamic education, which emphasizes the balanced assessment of cognitive, affective, and psychomotor domains. This study aimed to analyze the implementation of learning evaluation in Indonesian language subjects from an Islamic educational perspective among Grade V students at SDN 16 Bengkulu City. A descriptive qualitative approach was employed, involving Indonesian language teachers and students as research participants. Data were collected through observation, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that learning evaluation was conducted through both test and non-test assessments; however, test-based evaluation remained more dominant. Non-test assessments, particularly those related to language skills and character development, were not implemented and documented optimally. Several challenges were identified, including limited instructional time, inconsistency in non-test assessment practices, and remedial activities that primarily relied on retesting. From an Islamic educational perspective, these findings indicate that the evaluation process has not fully reflected a holistic assessment that integrates knowledge, skills, and character. Therefore, strengthening authentic assessment practices and improving the implementation of non-test evaluation are necessary to support more comprehensive student development.